Pengaruh Metode Pembelajaran Bercerita dan Berbasis Proyek Terhadap Kemampuan Berbahasa Anak Usia Dini Usia 5-6 Tahun: THE INFLUENCE OF PROJECT-BASED AND STORY LEARNING METHODS ON THE LANGUAGE ABILITY OF CHILDREN AGED 5-6 YEARS - ARI WULANDARI; RIVO PANII YUDHA (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
The poor ability to speak and tell stories can be seen from the difficulty in answering simple questions from the teacher. The weak ability of students to express their thoughts usually causes them to be quiet at school and unable to answer the teacher's questions. From childhood, he was also expected to understand other languages. Understanding conversation is a basic ability of students to adapt to the social environment. Because children aged 5-6 years usually have started communicating verbally with their environment and most children in kindergarten already have more than 8000 words. Therefore we need a learning model that can improve children's language skills. Until now, narrative models are considered suitable for improving children's language skills. However, the project-based learning model is a learning model that can also improve language skills in a more interesting way. These two models are compared to determine which model is more effective in improving early childhood language skills based on gender. The research was conducted at TK Bina Pendidikan Pekanbaru on children aged 5-6 years and the research method used was quantitative with two way ANOVA. The results showed that gender had no effect on language skills in early childhood. The role of teachers and parents is very important in children's language development. In improving children's language skills. To achieve good language skills, teachers must be creative and adapt the methods used to the character and needs of each child.